PELAKSANAAN PEMBUATAN PETA LENGKAP BERBASIS DESA UNTUK MEWUJUDKAN SISTIM INFORMASI PERTANAHAN DI KANTOR PERTANAHAN KABUPATEN BOYOLALI - YUSRI, YUSRI (Dinamika Hukum, 2018)
This research is to study and to know the suitability of the implementation of making the Complete Village Based Map in Boyolali District conducted by the Land Office of Boyolali Regency of Central Java Province with PMNA / KBPN Number 3 Year 1997 on Implementation of Government Regulation Number 24 Year 1997 in the field of national scale standard map provide the necessary information and to find out the constraints faced in implementing the village-based complete Map and the efforts made for the smooth implementation. The research method used is discrete method. The type of data obtained is Primary data is data obtained directly from the informant or data sources through interviews and documentation and secondary data is data obtained by observing and studying existing data relating to the implementation of making Village-Based Complete Map. Data collection techniques with documentation and interviews are then analyzed in a descriptive way with Qualitative approaches, by finding the distinction between the procedure of performing the Complete Village-Based Complete Map with the applicable regulations then analyzed, assessed and drawn a conclusion. The implementation of the Map-Based Complete Map in Boyolali District, Central Java, which has 19 Districts and 269 Villages, is carried out in stages. Implementation of Making Village-Based Complete Map there are things that the author wants to know and review about some things whether it is in accordance with the applicable regulations or not yet that is about the standard national scale maps that can provide the required information and the exact obstacles encountered in the implementation making the Village-based Complete Map which includes: Internal constraints / from within which is the lack of time, tools used and personnel / human resources implementing making Village-Based Complete Map. External / external constraints include the involvement of landowners, village apparatuses, unpinned land titles, land ownership disputes, inheritance distribution and many other external constraints that may hamper the implementation of a Village-Based Complete Map that can trigger land disputes in the future . Keywords: Making a complete village-based map that can provide information needed for the public interest.